Impact of electroweak corrections on neutral Higgs boson decays in extended Higgs sectors - Marcel Krause; Margarete Mühlleitner (Journal of High Energy Physics, 2020)
Abstract Precision predictions play an important role in the search for indirect New Physics effects in the Higgs sector itself. For the electroweak (EW) corrections of the Higgs bosons in extended Higgs sectors several renormalization schemes have been worked out that provide gauge-parameter-independent relations between the input parameters and the computed observables. Our recently published program codes 2HDECAY and ewN2HDECAY al- low for the computation of the EW corrections to the Higgs decay widths and branching ratios of the Two-Higgs-Doublet Model (2HDM) and the Next-to-Minimal-2HDM (N2HDM) for different renormalization schemes of the scalar mixing angles. In this paper, we present a comprehensive and complete overview over the relative size of the EW corrections to the branching ratios of the 2HDM and N2HDM neutral Higgs bosons for different applied renormalization schemes. We quantify the size of the EW corrections of Standard Model (SM)- and non-SM-like Higgs bosons and moreover also identify renormalization schemes that are well-behaved and do not induce unnaturally large corrections. We furthermore pin down decays and parameter regions that feature large EW corrections and need further treatment in order to improve the predictions. Our study sets the scene for future work in the computation of higher-order corrections to the decays of non-minimal Higgs sectors.